Radiotelephony Untuk Personel Pangkalan TNI AU Atang Sendjaja - Rosmayanti, Lina; Djoko Jatmoko; Sri Rahayu Surtiningtyas; Rany Adiliawijaya Putriekapuja; Ichyu Machmiyana; Ikhsan Wahyu Vebriyan; Ahmad Faridan (Jurnal Pengabdian Kepada Masyarakat, 2024)
In the aviation industry, radiotelephony is the primary communication tool between pilots and personnel involved in aircraft operations. According to the Director General of Civil Aviation Regulation Number KP 038 of 2017, personnel providing apron management services are required to have specific licenses, such as Air Traffic Controllers, Aeronautical Communication Officers (ACO), or Apron Movement Controllers (AMC), with additional skills in radiotelephony. However, the personnel at the Atang Sendjaja Air Force Base currently do not meet the radiotelephony competency requirements. To perform services according to national and international standards, the use of radiotelephony is essential. To address this need, a training program was conducted as part of a community service initiative, aimed at equipping personnel with radiotelephony skills in line with applicable regulations. This training includes both theoretical and practical sessions conducted on-site, utilizing table-top exercise simulation methods. The outcome of this training indicates that the personnel at the Atang Sendjaja Air Force Base have acquired adequate skills to implement radiotelephony in their daily operational activities.